FAKTOR-FAKTOR YANG MEMPENGARUHI STOCK RETURN PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - BILLIE ONGGO; WIDYAWATI LEKOK (Jurnal Bisnis dan Akuntansi, 2017)
The purpose of thus research is to obtain empirical evidence about the factors that influence stock return in the non-financial companies in Indonesia Stock Exchange. Independent variables used in this research are Human Capital efficiency, Structural Capital Efficiency, Capital Employed Efficiency, Return On Equity, Revenue Growth, Market to Book Value, Cash Flow from Operation. The populations used in this study are non-financial companies in Indonesia Stock Exchange during 2013-2015. This study used purposive sampling method with 130 companies as 385 datas according to criterias. Data are analyzed using multiple regression analysis. The result shows Human Capital efficiency, Structural Capital Efficiency, Capital Employed Efficiency, Return On Equity, Revenue Growth, Market to Book Value, Cash Flow from Operations toward stock return